Comparison of Physicochemical Properties of LipoParticles as mRNA Carrier Prepared by Automated Microfluidic System and Bulk Method - Camille Ayad; Altan Yavuz; Jean-Paul Salvi; Pierre Libeau; Jean-Yves Exposito; Valentine Ginet; Claire Monge; Bernard Verrier; Danielle Campiol Arruda (MDPI AG, 2022)
Polymeric and/or lipid platforms are promising tools for nucleic acid delivery into cells. We previously reported a lipid-polymer nanocarrier, named LipoParticles, consisting of polylactic acid nanoparticles surrounded by cationic lipids, and allowing the addition of mRNA and cationic LAH4-1 peptide at their surface. Although this mRNA platform has shown promising results in vitro in terms of mRNA delivery and translation, the bulk method used to prepare LipoParticles relies on a multistep and time-consuming procedure. Here, we developed an automated process using a microfluidic system to prepare LipoParticles, and we compared it to the bulk method in terms of morphology, physicochemical properties, and ability to vectorize and deliver mRNA in vitro. LipoParticles prepared by microfluidic presented a smaller size and more regular spherical shape than bulk method ones. In addition, we showed that the total lipid content in LipoParticles was dependent on the method of preparation, influencing their ability to complex mRNA. LipoParticles decorated with two mRNA/LAHA-L1 ratios (1/20, 1/5) could efficiently transfect mouse DC2.4 cells except for the automated 1/5 assay. Moreover, the 1/5 mRNA/LAHA-L1 ratio drastically reduced cell toxicity observed in 1/20 ratio assays. Altogether, this study showed that homogeneous LipoParticles can be produced by microfluidics, which represents a promising platform to transport functional mRNA into cells.